Evaluation of wastewater surveillance for SARS-CoV-2 in Massachusetts correctional facilities, 2020–2022 - Klevens, R. Monina; Young, Cristin C. W.; Olesen, Scott W.; Osinski, Anthony; Church, Daniel; Muten, Jennifer; Chou, Lori; Segal, Tami; Cranston, Kevin (Frontiers in Water, 2023)
Introduction: Correctional facilities have environmental, resource, and organizational factors that facilitate SARS-CoV-2 transmission and challenge clinical testing of staff and residents. In Massachusetts, multiple state prisons implemented wastewater surveillance for strategic testing of individuals and isolation of cases early in the course of infection, as recommended by the CDC. Our objective was to quantify the association of facility-level wastewater surveillance compared to standard case surveillance in the most proximal town. Materials and methods: Available data included number of reported COVID-19 resident cases from each of eight participating facilities (A-H), wastewater viral concentrations at each facility, and COVID-19 cases reported to routine surveillance in the closest town. We selected data from December 2020-February 2022. Data on staff cases were unreliable and not examined for this analysis. Spearman’s rank correlation was calculated at each facility to assess agreement between town cases and facility resident cases, and between wastewater concentrations and facility resident cases. We considered a correlation of ≤0.3 as weak and ≥0.6 as strong. Results: Facilities housed a mean of 502 individuals (range 54-1,184) with mean staffing of 341 (range 53-547). In 7/8 facilities, the town/resident cases correlation coefficients (ρ) were statistically significant (range 0.22-0.65); in all facilities, the wastewater/facility resident cases correlation were statistically significant (range 0.46-0.74). Consistently, ρ values were higher for facility-specific wastewater/resident cases than for town/resident cases: A (0.61, 0.74), B (0.66, 0.72), C (0.59, 0.61), D (0.55, 0.68), E (0.46, 0.51), F (0.42, 0.46), and H (0.22, 0.47). Conclusion: Correctional facilities could benefit from timely, unbiased identification of circulating virus. A consistently higher correlation between wastewater concentration and resident infections suggests facility-specific wastewater surveillance can be a useful supplement to community and facility case surveillance.